Sinkronisasi UUPA Terhadap Peraturan Perundang-Undangan di Bidang Penetapan dan Penggunaan Hak Atas Tanah - Tuharea, Farida; Sari, Liani; Kurnia Katjong, Revie; Irsan, Irsan; Tuhumury, Harry A.; Nurlia Mamonto, Andi Annisa (UNES Law Review, 2024)
In achieving what is emphasized in article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia, it is neither necessary nor appropriate for the Indonesian people or the State to act as land owners, it is more appropriate if the State, as the power organization of the entire people (nation) acts as the Body. Ruler. It is from this angle that we must look at the meaning of the provisions in article 2 paragraph 1 of the UUPA which states that "Earth, water and space, including the natural wealth contained therein, are at the highest level controlled by the State". In accordance with the principles stated above, the word "controlled" in this article does not mean "owned", but is an understanding, which gives authority to the State, as the ruling organization of the Indonesian Nation, to at the highest level regulate and carry out the allocation, use , provision and maintenance thereof, determines and regulates the rights that can be had over (part of) the earth, water and space, determines and regulates legal relationships between people and legal actions concerning earth, water and space. Understanding the concept of the meaning and substance of the state's right to control land is important to straighten out existing authority in the form of regulating, administering/managing and supervising to avoid confusion and arbitrariness. The right to control from the state is "the term given by the UUPA to legal institutions and the concrete legal relationship between the state and Indonesian land